Production of Aspergillus niger spores in submerged fermentation. - Abu Bakar, Radin Muhammad Arif (2010)
Fungal spores are widely used in bioindustry as inoculum for fermentation process,starter culture for biofertiliser and also biopestisides. The spores are normally produced via solid state fermentation when face with difficulty in the fermentation harvest process in order to control the consistent production of quality spores. The possibility of producing large amount of spores using small scale bioreactor in submerged fermentation was investigated in this study. The quality of spores and the kinetic of their germination are greatly influenced by the qualitative and quantitative description of the fermentation culture. Submerged conidiation occur the best in the absence or exhaustion of nitrogen, when carbon supply is assimilable. During cultivation, low concentration of carbon sources is also required as higher concentration above critical level will force the fungi to stay in vegetative form. This study focused on investigation the suitability of several carbon and nitrogen sources for production of Aspergillus niger FPC5003 spores in submerged shake flask culture. Among the carbon sources (glucose, sago corn and soluble starch) and nitrogen sources (yeast extract, bactopeptone, (NH4)2SO4, NaNO3, and NH4S2O4) tested, sago starch and yeast extract provide better option for spores production. During the experiments, different concentrations were used in the media. The spores production gave the highest yield (9.06 x 105 spores/mL) when cultivated in the media with 10g/L sago starch and 0.3g/L yeast extract. The spores production showed and increased of ten fold (1.26 x 106 spores/mL) when fed-batch culture being applied with sequential addition of carbon source under the critical level. The optimum production of A. niger FPC5003 spores can be achieved by providing suitable carbon and nitrogen sources and single temperature shift strategy during fermentation under provided condition, the final spores count obtained (6.09 x 107 spores/mL) was about 232% higher than when temperature was maintained at 30°C throughout the process (9.06 x 105) spores/mL). Item Type: Thesis (Masters)